a = 2 - [tex] \frac{1}{3} [/tex] (amplificam pe 2 c 3 si obtinem
a = [tex] \frac{6-1}{3} [/tex]
a = [tex] \frac{5}{3} [/tex]
b = 2 + [tex] \frac{1}{3} [/tex]
b = [tex] \frac{6+1}{3} [/tex]
b = [tex] \frac{7}{3} [/tex]
a+b = [tex] \frac{5}{3} [/tex] + [tex] \frac{7}{3} [/tex]
a+b = [tex] \frac{12}{3} [/tex]
a+b = 4
b -a = [tex] \frac{7}{3} [/tex] - [tex] \frac{5}{3} [/tex]
b-a = [tex] \frac{2}{3} [/tex]
a*b = [tex] \frac{5}{3} [/tex] * [tex] \frac{7}{3} [/tex]
a*b = [tex] \frac{35}{9} [/tex]
a / b = [tex] \frac{5}{3} [/tex] / [tex] \frac{7}{3} [/tex]
a / b = [tex] \frac{5*3}{7*3} [/tex]
a / b = [tex] \frac{15}{21} [/tex] (simplificam fractia cu 3
a / b = [tex] \frac{5}{7} [/tex]